Efficacy and safety of glimepiride as initial treatment in Russian patients with type 2 diabetes mellitus - Alexander Sergeevich Ametov; Fatima Totrazovna Abaeva (Сахарный диабет)
Aim.  To investigate the efficacy and safety of glimepiride as initial mono-therapy in type 2 diabetes patients (T2DM). Materials and Methods. This is a multi-center, open-label prospective observational study. 245 treatment-naive T2DM patients, who had not achieved glycemic goals on lifestyle therapy during first 12 weeks after the diagnosis, were enrolled in this study. Anti-diabetes treatment was initiated with glimepiride and continued during the 6-month follow-up period. Prescription of the initial dose (1 mg per day) and further dose adjustments were carried out by the attending physician in accordance with the glimepiride data sheet. Dynamics of HbA1c, fasting plasma glucose (FPG), 2 h postprandial blood glucose (2hPPG), weight and waist circumference, as well as the incidence of hypoglycemia were the evaluated parameters. Results. The baseline HbA1c (mean: 7.9?0.5%; female: 7.8?0.4% ; male: 8.0?0.6%) was significantly reduced at week 12 (mean 7.2?0.6%, p